2014
DOI: 10.3389/fphys.2014.00448
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating the cost of growth and swimming in fish—the applicability of exercise-induced growth to juvenile hapuku (Polyprion oxygeneios)

Abstract: Induced-swimming can improve the growth and feed conversion efficiency of finfish aquaculture species, such as salmonids and Seriola sp., but some species, such as Atlantic cod, show no or a negative productivity response to exercise. As a possible explanation for these species-specific differences, a recent hypothesis proposed that the applicability of exercise training, as well as the exercise regime for optimal growth gain (ERopt growth), was dependent upon the size of available aerobic metabolic scope (AMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…However, there may be species‐specific differences in energy allocation and biomass gain in relation to activity (Khan et al, ). A previous study from Monk, Puvanendran, and Brown () reported that no significant differences between growth and survival, as shown by foraging behaviour such as swimming of Atlantic cod ( Gadus morhua ) when reared in two different colours, beige (light colour) or black (dark colour).…”
Section: Discussionmentioning
confidence: 99%
“…However, there may be species‐specific differences in energy allocation and biomass gain in relation to activity (Khan et al, ). A previous study from Monk, Puvanendran, and Brown () reported that no significant differences between growth and survival, as shown by foraging behaviour such as swimming of Atlantic cod ( Gadus morhua ) when reared in two different colours, beige (light colour) or black (dark colour).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, fish species may be able to exercise constantly at velocities between 0.5 and 2 BL s À1 without any decline in growth rate, by compensating with increased feed intake. This, of course, implies progressively reduced feed efficiency and FCR as swimming speed increases (Kiessling et al, 1994(Kiessling et al, , 2005Khan et al, 2014;Skov et al, 2015; Table 1). It is conceivable, nonetheless, that FCR and growth 'efficiency' are improved in exercised fish compared with those held in still water (Christiansen & Jobling, 1990;Jobling et al, 1993;Shrivastava et al, 2018).…”
Section: Sparus Auratamentioning
confidence: 99%
“…Swimming exercise can stimulate appetite (Fig. 2) to match the increased metabolic demands of locomotion, such that growth is not compromised or is even increased (Leon, 1986; Totland et al, 1987; Christiansen & Jobling, 1990; Jørgensen & Jobling, 1993; Khan et al, 2014; Skov et al, 2015; Li et al, 2016). In fact, fish species may be able to exercise constantly at velocities between 0.5 and 2 BL s −1 without any decline in growth rate, by compensating with increased feed intake.…”
Section: Exercise and Production: Effects On Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sustained exercise resulted in augmented growth in: brown trout (Salmo trutta; Davison and Goldspink, 1977), rainbow trout (Oncorhynchus mykiss; Walker and Emerson, 1978;Nahhas et al, 1982;Houlihan and Laurent, 1987), Atlantic salmon (Salmo salar; Kuipers, 1982;Totland et al, 1987), Arctic charr (Salvelinus alpinus; Christiansen et al, 1989;Christiansen and Jobling, 1990) and brook trout (Salvelinus fontinalis; Leon, 1986;East and Magnan, 1987). Exercise-induced growth has also been reported for non-salmonids such as gilthead seabream (Sparus aurata; Ibarz et al, 2011;Sánchez-Gurmaches et al, 2013), striped bass (Morone saxatilis; Young and Cech Jr, 1993), qingbo (Spinibarbus sinensis; Li et al, 2013), hapuku (Polyprion oxygeneios; Khan et al, 2014), pacu (Piaractus mesopotamicus; Nunes et al, 2013), zebrafish (Danio rerio; Palstra et al, 2010) and yellow tail kingfish (Seriola lalandi; Brown et al, 2011;Palstra et al, 2015).…”
Section: Introductionmentioning
confidence: 98%